Diversification of the competitive position of the advanced technology sector in EU - Małgorzata Juchniewicz; Magdalena Łada (International Journal of Management and Economics, 2020)
The high-technology sector has a particular importance in the development of modern national economies. It affects both the level of competitiveness and innovation. This was a prerequisite for the study to assess the competitive position of the advanced technology sector in the European Union (EU) countries. The starting point of the discussion was the definition of the concept of competitiveness, the competitive position of the advanced technology industry, and the classification of the high-tech sector. Based on the selected indicators, the competitive position and the rank of countries have been established. As for this, the indicators of the export share of the advanced technology sector in the intra-export market, the profitability of the high-tech sector, and the degree of export-import coverage were used. Based on the adopted indicators, a synthetic indicator of a competitive position has also been calculated which enabled determination of the most competitive country in the EU in reference to the industry. This enabled the identification of factors influencing the competitive position of the advanced technology sector in the EU member countries.
Keywords: O1; O3; 650; competitive position; industry; advanced technologies; European Union